Effects of coronavirus disease-2019 on voice: our experience of laryngeal complications following mechanical ventilation in severe coronavirus disease-2019 pneumonitis and review of current literature. Issue 6 (December 2021) - Watson, Natalie A.; Karagama, Yakubu; Burnay, Victoria; Boztepe, Selda; Warner, Susan; Chevretton, Elfy B.
Abstract : Purpose of review: Dysphonia has been described as a major symptom of coronavirus disease-2019 (COVID-19). A literature review examining this topic was undertaken and is presented here, combined with insights from our experience in managing patients with laryngeal complications following mechanical ventilation for severe COVID-19 pneumonitis. Recent findings: Naunheim et al. reported that patients who are most at risk of needing intubation with COVID-19 disease are those with patient-specific risk factors and these are at an increased risk for subsequent laryngotracheal injury following intubation (1). In our cohort of 105 patients referred with laryngological symptoms postintubation for COVID-19 pneumonitis, 40% presented as urgent reviews, of which almost half had severe postintubation complications requiring surgery. Perceptual voice ratings and patient-reported voice ratings varied widely, but there was no significant change in voice scores postoperatively. The reflux symptom index (RSI) scores did improve significantly ( p = 0.0266). The need for surgery was associated with the presence of comorbidities for instance hypertension, diabetes and obesity in our cohort. This is in support of reported association of comorbidity as a risk factor for intubation and subsequent development of postintubation airway complications. Summary: Dysphonia following COVID-19 infection may have multiple causes. Literature reports demonstrate intubation injury, sensory neuropathy, and postviral neuropathy are associated with voice changes. Our personal experience has confirmed postintubation injury markedly affects glottic function with resultant dysphonia attributable to scar formation, posterior glottic stenosis, granulation and subglottic stenosis. Frequent surgical intervention is required for airway patency and may have short-term further deleterious effects on phonation, although in our cohort this is not statistically significant analysing Grade, Roughness, Breathiness, Asthenia, Strain, Voice Handicap Index-10 or Airway, Voice, Swallow scores. Maximal antireflux medications and advice statistically improved RSI scores postoperatively.